The 'other' identity : analysis of cultural patterns in female body disorders - Assumpta Rigol Cuadra (Universidad de Alicante, 2012)
The present study focuses in the way a body identity is built up from a social and cultural perspective in anorexia nervosa. Different authors, a feminist perspective of health and anthropological points of view are taken into consideration. Both concepts - social and cultural - present a wider vision of mental disorders and suggest to approach the problem within the contest of a cultural illness. Aim: To analyse and compare variables of cultural patterns in our society regarding female identity considering as paramount the 'body' point of view. Being the first consideration that coming from women diagnosed of anorexia. Methodology: Qualitative research, in-depth interviews and observation were the basic techniques used. Results: As various categories were observed three large groups were considered according to: perception of identity; social perception of the body; and acceptability of one's own body. Conclusions: It would be wise to express that female identity patterns suggested as an ideal image and the means to achieve those patterns enters into a real conflict difficult to escape as much for normal women as for those diagnosed of anorexia nervosa.